2018
DOI: 10.1152/physiolgenomics.00122.2017
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus infection induces distinct transcriptome profiles in polarized human macrophages

Abstract: Infections with rhinovirus (RV) cause asthma exacerbations. Recent studies suggest that macrophages play a role in asthmatic airway inflammation and the innate immune response to RV infection. Macrophages exhibit phenotypes based on surface markers and gene expression. We hypothesized that macrophage polarization state alters gene expression in response to RV infection. Cells were derived from human peripheral blood derived monocytes. M1 and M2 polarization was carried out by using IFN-γ and IL-4, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…These findings are in line with a recent study by Rajput, et al . 37 who observed higher responsiveness to rhinovirus infection in M1-primed macrophages compared to M2-primed macrophages, which was associated with higher expression of MDA5. In our study, RV-induced expression of TLR3 was reduced in human M2-like macrophages compared to M1-like ones.…”
Section: Discussionmentioning
confidence: 95%
“…These findings are in line with a recent study by Rajput, et al . 37 who observed higher responsiveness to rhinovirus infection in M1-primed macrophages compared to M2-primed macrophages, which was associated with higher expression of MDA5. In our study, RV-induced expression of TLR3 was reduced in human M2-like macrophages compared to M1-like ones.…”
Section: Discussionmentioning
confidence: 95%
“…Little is known about the effect of HRV infection on macrophage phagocytosis, although recent data suggest other respiratory viruses, such as influenza and respiratory syncytial virus, may decrease bacterial uptake in human macrophages (18). Although previous work has predominantly focused on epithelial cells, which are the primary site of HRV replication (19), HRV may induce distinct transcriptome profiles, which are driven toward a proinflammatory phenotype in polarized human macrophages (20) and to alter the activation status of AM in a mouse model of asthma exacerbations (21).…”
mentioning
confidence: 99%
“…HPV detected in the rectal squamous cell carcinoma is associated with the increased macrophage M2 polarization 31 . In addition, the swine influenza virus 32 and rhinovirus 33 can also be involved in the regulation of macrophage conversion from M1 to M2 polarization. Saha et al 34 also found that hepatitis C virus can induce monocytes to differentiate into polarized M2 macrophages, which promotes the activation of stellate cells by TGF-β.…”
Section: Discussionmentioning
confidence: 99%